Novel pathogenic mechanisms of porcine reproductive and respiratory syndrome virus: intercellular transmission and persistence - Guo, Rui (Kansas State University, 2018)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes a tremendous economic loss in swine industry worldwide. The capabilities to evade host immune responses and to establish persistent infection are the two hallmark features of PRRSV infection. In this dissertation, the research was mainly focused on investigating the novel mechanisms underlying PRRSV transmission and persistence. In chapter 2, the research was focused on an alternative pathway of PRRSV intercellular transmission. Our data showed that intercellular nanotube connections can be utilized for cell-to-cell spreading the core infectious viral machinery (viral RNA, certain replicases and structural proteins) of PRRSV. Live-cell movies tracked the intercellular transport of a recombinant PRRSV that expressed green fluorescent protein (GFP)-tagged nsp2 in a receptor-independent manner. The cytoskeleton proteins F-actin and myosin-IIA were identified as co-precipitates with PRRSV nanotube associated proteins. Drugs inhibiting actin polymerization or myosin-IIA activation prevented nanotube formations and viral clusters in virus-infected cells. These data lead us to propose that PRRSV utilizes the host cell cytoskeletal machinery inside nanotubes for efficient cell-to-cell spread. This form of virus transport represents an alternative pathway for virus spread, which is resistant to the host humoral immune response. In chapter 3, we further showed that PRRSV infection could induce the formation of nanotubes between infected and uninfected cells following a ROS-dependent nanotube formation model. Co-culturing PRRSV-infected cells with uninfected cells rescued PRRSV-induced cell death. Mitochondrion was observed transferring from uninfected to PRRSV-infected cells. Importantly, impaired formation of nanotube or defective mitochondrion was unable to rescue infected cells from apoptosis/necrosis. Certain PRRSV proteins were detected to associate with mitochondria and transport from infected to uninfected cells through TNTs. Our results suggest that TNTs-transfer of functional mitochondria rescued PRRSV-infected cells from apoptosis/necrosis in the early stage of infection. On the other hand, mitochondria could be utilized as a cargo to transport viral materials for spreading the infection. In chapter 4, a novel mechanism s of PRRSV persistent infection has been studied. In this study, a cellular model of persistent infection was established. Strand-specific quantitative RT-PCR and RNase I treatment analysis showed that double-stranded RNA (dsRNA) conformation existed in persistently infected cells. This data has been further confirmed in vivo by performing two independent PRRSV persistence studies. Immunohistochemistry analysis showed that viral dsRNAs were detected aggregating inside the germinal centers of tonsils and lymph nodes from PRRSV persistence pigs, but RNA array analysis further showed that dsRNA in lymphoid tissues had limited ability to stimulate host antiviral responses during persistent infection stage. These results suggest that the PRRSV dsRNA functions as a mediator for viral persistence. The viral dsRNA persistence in germinal centers of lymphoid tissues may reveal a novel mechanism for PRRSV to escape antiviral immune responses. In summary, this study investigated two novel pathogenic mechanisms of PRRSV infection, which could provide insights on the development of effective control strategies.
Keywords: PRRSV; Pathogenic mechanisms; Transmission; Persistence